.6a+2=.3+4+4+4+4+1

Simple and best practice solution for .6a+2=.3+4+4+4+4+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .6a+2=.3+4+4+4+4+1 equation:


Simplifying
0.6a + 2 = 0.3 + 4 + 4 + 4 + 4 + 1

Reorder the terms:
2 + 0.6a = 0.3 + 4 + 4 + 4 + 4 + 1

Combine like terms: 0.3 + 4 = 4.3
2 + 0.6a = 4.3 + 4 + 4 + 4 + 1

Combine like terms: 4.3 + 4 = 8.3
2 + 0.6a = 8.3 + 4 + 4 + 1

Combine like terms: 8.3 + 4 = 12.3
2 + 0.6a = 12.3 + 4 + 1

Combine like terms: 12.3 + 4 = 16.3
2 + 0.6a = 16.3 + 1

Combine like terms: 16.3 + 1 = 17.3
2 + 0.6a = 17.3

Solving
2 + 0.6a = 17.3

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 0.6a = 17.3 + -2

Combine like terms: 2 + -2 = 0
0 + 0.6a = 17.3 + -2
0.6a = 17.3 + -2

Combine like terms: 17.3 + -2 = 15.3
0.6a = 15.3

Divide each side by '0.6'.
a = 25.5

Simplifying
a = 25.5

See similar equations:

| 40x+80=70x+125 | | x(x-14)=-7(4x+7) | | 47+3y-21=12y-9-4y | | 4/3n=36 | | 9x^2-36x+29=0 | | 40x+800=70x+1250 | | 7c-8+3(c-9)=-75 | | 6x^2-12x-11=0 | | (x+7)(3x+4)=-14 | | 5-3x=12-6x | | 7x+1=(4x+4) | | 14-9y=-13 | | 2/7k-1/14=-3 | | 459=16x+7 | | 3x(3x+2)=35 | | m-61/4=93/8 | | u^2-9/169 | | -3/7p=36 | | y-4=5/4(x+8) | | 11.3=452 | | 15=9h | | 3m=-45 | | x(20x+21)=54 | | X^2+6x+8=99 | | 3(2x+3)=5/2+2(x+1) | | 2k+3k=120 | | x^2+3y^2+4x+6y+7=0 | | -1/6m-5/8+3/4m=7/4 | | -7/3h=35 | | -1/6m-5/8+3/4m=13/4 | | 5n+7=5+3n | | y-4=5/4(x-1(-8)) |

Equations solver categories